Method for the multi-criteria optimization of car wheel suspension mechanisms (2016)
The paper deals with a general method for the multi-criteria optimization of the rear wheels suspension mechanisms in terms of kinematic behavior. The suspension mechanism is decomposed in basic binary links, and the kinematic synthesis is separately performed for each of them. The design variables are the global coordinates of the joint locations on the car body (chassis). The disposing of the joints on the wheel carrier were exclusively established by constructive criteria. The design objectives relate to kinematic position parameters of the wheel (displacements of the wheel centre along longitudinal and transversal directions, and modifications of the wheel axis direction), the optimization goal being to minimize these variations during the wheel travel. A computer program for the kinematic study was developed in C++. The application was performed for the wheel suspension mechanism of a race car.